An Inside Sun: Lickanantay Volcanology in the Salar de Atacama - Ramos Chocobar, Sonia; Tironi, Manuel (Frontiers in Earth Science, 2022)
The Salar de Atacama Basin is an active volcanic territory and considered a “hotspot” within the Central Volcanic Zone of the Andes (CVZA). From El Tatio geothermal field to Socompa, more than 19 active volcanoes surround a territory that the Lickanantai (Atacameño) people have inhabited for more than 11,000 years. Living around and with the geological dynamism of the CVZA for millennia, Lickanantai communities have accumulated rich observational and ceremonial data on volcanoes and volcanism. Paradoxically, however, while Atacameño people have thoroughly characterized the CVZA, the volcanology community has not been properly introduced to the time-tested and situated knowledge articulated in the territory. In order to make available to the volcanology community traditional Atacameño perspectives on volcanoes, volcanic risk, and geo-cosmic interdependence more amply, in this paper we present a basic description of what we call Atacameño volcanology. By Atacameño volcanology we understand the ancestral principles by which volcanoes are known and understood as partaking in larger processes of cosmo-ecological formation. Specifically we describe, first, the basic volcanological notions arising from Lickanantai ancestral knowledge —volcanic formation, functions, and behavior. Second, we zoom-in to the case of El Tatio geothermal field to offer a situated example. Finally, we delineate some relevant elements of human-volcano interactions and volcanic risk management from an Atacameño perspective. In our conclusions we suggest that Western volcanology, particularly in the context of the Andes, needs to engage more substantially with Atacameño or otherwise ancestral systems of knowledge production to expand volcanological insights and respond to the call for decolonizing science.